Preparation of students and teachers of physical education to work with children with cancer - Anna Bochenek; Monika Ewa Drogosiewicz; Katarzyna Sierpotowska (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
Introduction: A physical education teacher in a modern school should have many competences to work with a student with chronic illness, including a student after anticancer therapy. The role of physical activity for cancer survivors is enormous. Therefore, this student should not be released from participation in school physical education, but every effort should be made to make physical activity an element of his lifestyle until late old age. Material and methods: The aim of the research is to diagnose the level of preparation of students and teachers of physical education to work with children with cancer. The group of respondents was 172 physical education teachers and 672 students completing physical education studies. The research used the author's questionnaire. Results: Respondents do not feel prepared to work with a child after cancer and almost everyone wants to expand their knowledge in this area. Half of the respondents do not know what is the role of physical activity in the life of cancer survivors, about 30% do not know whether children after cancer treatment can participate in physical education. Conclusions: Changes should be introduced in the process of educating physical education teachers to prepare them for work with a child after cancer treatment. It is necessary to create an offer of trainings raising the competences of physical education teachers to work with children with chronic disease.